PERSEPSI ATAS GAYA KEPEMIMPIAN KEPALA SEKOLAH DAN TIPE KEPRIBADIAN TERHADAP KINERJA GURU - Annisa Zatil Aqmar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract: The purpose of this study is to determine the role of perception of the leadership style applied by school principals and personality types on teacher performance. The research method used in this thesis is a quantitative method. The study population included all teachers in SMK Global Paskita, SMK Mahadia 4 and SMK PGRI 16. The sampling technique used was simple random sampling with Slovin technique and the number of samples were 80 samples. Data collection uses a questionnaire while data analysis uses correlation coefficient and regression analysis, which is connecting data that shows the effect of perception of the principal's leadership style and personality types on teacher performance. data on perceptions variables on the principal's leadership style, personality type and teacher's performance were obtained through a questionnaire prepared by the researcher. Hypothesis test results indicate: There is a significant influence of perception of leadership style and personality types together on teacher performance. There is no significant effect of perception of leadership style on teacher performance. There is a significant influence of personality type on teacher performance. Keywords: Perception of Principal's leadership style, Personality Type, Teacher Performance